Car Brands Positioning in UEMC University Students: Differences in Perception based on Driving Experience - Tapia Frade, Alejandro (2011)
This paper provides an analysis of car brands positioning on a sample of UEMC university students. The statistical method used was simple correspondence analysis as part of a survey on the sample above mentioned. The results reveal the structure of the automobile market in all cases where several competing groups depending on the price. We also found significant differences in the midrange segment in both periods analyzed, both in the case of students driving license as in the case of students without such authorization.